Materiality judgments in an integrated reporting setting: The effect of strategic relevance and strategy map - Green, Wendy J.; Cheng, Mandy M. (Accounting, Organizations and Society, 2019)
This study reports an experiment conducted to examine auditors' materiality judgments for nonfinancial performance information (NFPI) in the context of Integrated Reporting; a setting where auditors do not have well-established guidelines or benchmarks. We examine two fundamental factors underlying Integrated Reporting that are predicted to influence auditors' NFPI materiality judgments, namely, the level of strategic relevance associated with the NFPI being assessed, and the provision of a strategy map (a visual representation of linkages between the firm's strategic objectives) to auditors. Our study provides evidence that while auditors judge misstated NFPI of low strategic relevance to be less material than misstated NFPI with high strategic relevance, they only make this distinction when a strategy map is present. As integrating a client's strategy in the process of evaluating materiality is important, our result suggests that the presence of a strategy map potentially improves the efficient allocation of assurance resources. The importance of understanding how qualitative factors affect materiality judgments in nonfinancial assurance engagements is reflected in the fact that accounting firms view such assurance as mainstream. Our findings not only have implications for standard setters developing further guidance for determining audit materiality under Integrated Reporting, but also more generally for auditors who are providing assurance services for NFPI.